2000
DOI: 10.1007/bf02344876
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a pure autologous biodegradable fibrin matrix for tissue engineering

Abstract: Parallel to the growing role of tissue engineering, the need for cell embedding materials, which allow cells to stabilise in a three-dimensional distribution, has increased. Although several substances have been tested, fibrin is thus far the only one that permits the clinical application of cultured tissue. To date, autologous fibrinogen has usually been polymerised with bovine thrombin, which can cause severe immunological side effects. The objective of this study was to explore the practicability of obtaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…Nevertheless, we have shown that the human fibrin gel system offers a potential patient-specific autologous scaffold for cartilage regeneration, since human fibrinogen and thrombin can be isolated separately from a patient's fresh plasma, and encapsulated cells can be donated by the same patient [Rock et al, 2001]. The advantage of a completely autologous approach for gel formation would be the elimination of the risk of tissue incompatibility and viral infection [Haisch et al, 2000] as well as an associated ease of transition to clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we have shown that the human fibrin gel system offers a potential patient-specific autologous scaffold for cartilage regeneration, since human fibrinogen and thrombin can be isolated separately from a patient's fresh plasma, and encapsulated cells can be donated by the same patient [Rock et al, 2001]. The advantage of a completely autologous approach for gel formation would be the elimination of the risk of tissue incompatibility and viral infection [Haisch et al, 2000] as well as an associated ease of transition to clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies have been performed with isolated/processed components, a possible advantage of using fibrin is that fibrinogen and thrombin, the precursors to fibrin gel formation, can be readily obtained from a patient's own blood [Haisch et al, 2000]. Like collagen gel-based grafts, constructs created from fibrin-gels have a typically low mechanical strength.…”
Section: Purified Proteins As Scaffoldsmentioning
confidence: 99%
“…The healing time for wound varies among different kinds of tissues, 12 and the biodegradable devices are required to maintain stability until wound heals. 13 Degradation/corrosion mechanism of the biodegradable materials which can be used as reference for biodegradable device design has received a lot of attention from the scientific community. There were many studies on the corrosion mechanism of Mg alloy as a biodegradable material.…”
Section: Related Workmentioning
confidence: 99%